Hooray for snail! - Stadler, John (Harper Collins, 1984)
Slow Snail hits the ball so hard during a baseball gaem that it flies to the moon and back. will Snail have time to slide in for home run?
Keywords: Snails -- Fiction; Baseball -- Fiction